MET expression and amplification in patients with localized gastric cancer - Janjigian, Yelena Y. (2011)
BACKGROUND: MET, the receptor for hepatocyte growth factor has been proposed as a therapeutic target in gastric cancer. This study assessed the incidence of MET expression and gene amplification in tumors of Western patients with gastric cancer. METHODS: Tumor specimens from patients enrolled on a preoperative chemotherapy study (NCI 5700) were examined for presence of MET gene amplification by fluorescence in situ hybridization (FISH), MET mRNA expression by quantitative polymerase chain reaction, MET overexpression by immunohistochemistry (IHC), and for evidence of MET pathway activation by p-MET IHC. RESULTS: Although high-level of MET protein and mRNA were commonly encountered (in 63% and 50% of resected tumor specimens, respectively), none of these tumors had MET gene amplification by FISH, and only 6.6% had evidence of MET tyrosine kinase activity by p-MET IHC. CONCLUSIONS: In this cohort of patients with localized gastric cancer, the presence of high MET protein and RNA expression does not correlate with MET gene amplification or pathway activation as evidenced by the absence of amplification by FISH and negative p-MET IHC analysis. IMPACT: This paper demonstrates a lack of MET amplification and pathway activation in a cohort of 38 patients with localized gastric cancer, suggesting that MET-driven gastric cancers are relatively rare in Western patients.